2010
DOI: 10.7205/milmed-d-10-00131
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Obstructive Sleep Apnea Syndrome and Microvascular Complications in Well-Controlled Diabetic Patients

Abstract: Screening for OSAS should be considered in patients with DM-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
2
40
2
Order By: Relevance
“…Furthermore, multifactor logistic regression analysis indicated that AHI, the gold standard for diagnosing OSAHS, was independently related to DN. These results are consistent with previous findings reported by other groups [25,26]. (2) The prevalence of DN in patients with mild OSAHS, moderate OSAHS, and severe OSAHS was higher than in patients without OSAHS; (3) AHI is positively correlated with UACR, while L-SaO 2 is negatively correlated with UACR; (4) With the increasing severity of OSAHS, patients with T2DM are more prone to affect DN.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, multifactor logistic regression analysis indicated that AHI, the gold standard for diagnosing OSAHS, was independently related to DN. These results are consistent with previous findings reported by other groups [25,26]. (2) The prevalence of DN in patients with mild OSAHS, moderate OSAHS, and severe OSAHS was higher than in patients without OSAHS; (3) AHI is positively correlated with UACR, while L-SaO 2 is negatively correlated with UACR; (4) With the increasing severity of OSAHS, patients with T2DM are more prone to affect DN.…”
Section: Discussionsupporting
confidence: 92%
“…In patients with type II diabetes who also have sleep apnoea with more than 5 dips per night, retinopathy is more severe and occurs earlier, than in a control groups matched for other variables [57][58][59]. Thus, even short periods of reduced oxygen supply to the retina exacerbate diabetic retinopathy.…”
Section: The Link Between Retinal Hypoxia and Retinal Damage In Diabetesmentioning
confidence: 88%
“…Several studies (n ¼ 31-92) showed that OSA and OSA severity are associated with poorer glycaemic control (HbA1c and/or fasting plasma glucose) despite adjustment for confounders (demographics, BMI, medications, exercise, diabetes duration, and total sleep time) in some studies [69,[73][74][75][76]. The adjusted mean increase in HbA1c between patients with and without OSA was 0.7-3.7% depending on the study population and OSA severity.…”
Section: Metabolic Controlmentioning
confidence: 99%